(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The growing needs for wood and the impact of forest ecosystems on the climate of the planet require the rational use of wood raw material. One possible way to "save" forests is to increase the use of agricultural lignocellulosic residues. The research efforts of scientists around the world are aimed at improving the properties of wood-based panels and to increase the share of agricultural residues in that production. In laboratory conditions were produced three-layer combined wood-based panels with a face layer of wood fibers and a core layer of wood and vine sticks particles. The participation of vine stick particles in the core layer was: 0; 15; 30 and 45%. As binder was used urea-formaldehyde resin. The content of resin in core layer was 8; 10; and 12%. The properties of the panels with and without participation of vine particles were compared. The final data for physical and mechanical properties of the panels, with participation of vine particles, were processed by the methods of regression analyze. In the result of conducted study was established and analyzed the influence of the participation of particles from vine stick and resin content on the physical and mechanical properties of combined wood-based panels.